2016
DOI: 10.1021/acs.est.5b05059
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Sensing Approach for Regional Surveillance of Fugitive Methane Emissions in Oil and Gas Production

Abstract: This paper addresses the need for surveillance of fugitive methane emissions over broad geographical regions. Most existing techniques suffer from being either extensive (but qualitative) or quantitative (but intensive with poor scalability). A total of two novel advancements are made here. First, a recursive Bayesian method is presented for probabilistically characterizing fugitive point-sources from mobile sensor data. This approach is made possible by a new cross-plume integrated dispersion formulation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 34 publications
1
69
0
Order By: Relevance
“…The filter was later used to mask and adjust the raw mixing ratio data to remove the adverse effects caused by this issue. The background methane mixing ratio (c b ) was estimated as the 5 th percentile of the ranked time series of raw methane mixing ratios (c r ) (Albertson et al, 2016;Brantley et al, 2014), and the above-ambient mixing ratios c = c rc b . The estimated c b is very close to the ambient methane mixing ratios measured upwind of the plant, suggesting that the determination of c b is robust.…”
Section: Field Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The filter was later used to mask and adjust the raw mixing ratio data to remove the adverse effects caused by this issue. The background methane mixing ratio (c b ) was estimated as the 5 th percentile of the ranked time series of raw methane mixing ratios (c r ) (Albertson et al, 2016;Brantley et al, 2014), and the above-ambient mixing ratios c = c rc b . The estimated c b is very close to the ambient methane mixing ratios measured upwind of the plant, suggesting that the determination of c b is robust.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Using data collected during multiple sensor passes, a Bayesian approach was adopted to characterize methane emission from the ammonia fertilizer plants. This approach is fully described in (Albertson et al, 2016); here only a brief introduction is included. Following Bayes's rule, the posterior probability density function (PDF) of the emission rate Q [kg/h] is (Albertson et al, 2016;Yee, 2008;Yee, 2012):…”
Section: Emission Characterization Using a Bayesian Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Referenced study uncertainty range* Ground-based thermal imaging Gålfalk et al (2016) 3-15 % Aircraft remote sensing Kuai et al (2016), Frankenberg et al (2016), Thorpe et al (2016) 5-20 % Satellite remote sensing Kort et al (2014) 15 % Chamber sampling Allen et al (2013Allen et al ( , 2014, Kang et al (2014) 20-30 % Ground-based tracer correlation Lamb et al (2015), Roscioli et al (2015), , Zimmerle et al (2015), Omara et al (2016) 20-50 % Aircraft/UAV mass balance Karion et al (2013Karion et al ( , 2015, Peischl et al (2013Peischl et al ( , 2015Peischl et al ( , 2016, Caulton et al (2014), Pétron et al (2014), Lavoie et al (2015), Nathan et al (2015) 20-75 % Ground-based stationary dispersion Brantley et al (2014), Foster-Wittig et al (2015 25-60 % Tall-tower monitoring Pétron et al (2012) 50-100 % Ground-based mobile dispersion Lan et al (2015), Rella et al (2015), Yacovitch et al (2015) 50-350 % * Uncertainty range reflects author-reported uncertainty on emission numbers, not necessarily measurement uncertainty. Some authors specify a 95 % confidence interval, others use 1 or 2 standard deviations and others compute upper and lower bounds.…”
Section: Reference Techniquementioning
confidence: 99%
“…Applications that have to characterize peaks of measurements can benefit. One of them is the problem of geo-locating leaks through a network of detector sensors [18] such as in the field of industrial pollution detection [19].…”
Section: Discussionmentioning
confidence: 99%